Design And Performance Analysis Of A WDM Packet Switching Network - Mellah, Hakim (2008)
This work proposes solutions to address two critical issues in synchronous OPS networks: contention resolution and physical limitations. For the first issue, a novel switch node structure designed for contention resolution in synchronous OPS network is proposed.